Radiological assessment of bauxite residue processing to enable zero-waste valorisation and regulatory compliance. (20th April 2021) - Goronovski, Andrei; Rivera, Rodolfo M.; Van Gerven, Tom; Tkaczyk, Alan H.
Abstract: In this work, the presence of natural radionuclides in bauxite residue subjected to a neutralisation-leaching process and smelting-leaching process was investigated. The radionuclide concentrations of radium-226, radium-228 and thorium-228 were compared with the concentration of the same radionuclides in the untreated bauxite residue. It was found that neutralisation of bauxite residue at relatively high temperatures (120–150 °C) and high pressure ( P CO2  = 30 bar) did not change the initial concentration of radionuclides. In fact, the concentration of radionuclides after an intensive neutralisation process remained below 500 Bq kg −1 . The separation of iron from the rare-earth elements by reductive smelting permitted a significant decrease of iron concentration in the pregnant leach solution obtained after high pressure acid leaching. However, the radionuclide concentration in the slag was increased 1.5 times with respect to the initial concentration, although it did not exceed 800 Bq kg −1 . Further processing of the slags by high pressure acid leaching led to the dissolution of several base metals, while a portion of the radionuclides remained unreacted in the solid fraction. Thus, a concentration of thorium-228 > 1000 Bq kg −1 was only observed after leaching a calcium oxide-based slag with hydrochloric acid. Meanwhile, in the leach liquors, the concentration of radionuclides was <100 Bq L −1 . Nevertheless, based on analytical estimations using conservative assumptions, the solid residues and leach liquors produced by acid leaching in the current study are unlikely to exceed the exposure limit of 1 mSv set by the European Basic Safety Standards Directive. It should be noted that the current results are based on a specific bauxite residue studied in this work, and caution should be used in the application to other situations. The described radiological assessment of bauxite residue processing can ensure the necessary regulatory compliance and facilitate zero-waste valorisation. Graphical abstract: Image 1 Highlights: Radionuclide concentration after neutralisation is the same as non-neutralised. Radionuclide concentration is 150% after separating Fe from the original sample. Solid residues can accumulate 228 Th above 1000 Bq kg −1 after leaching with HCl. Analytical model estimates less than 1 mSv/year dose for post-processed BR.